Faktor-faktor yang mempengaruhi penyertaan tenaga kerja belia tempatan dalam sektor perladangan sawit di Malaysia - Mohammad Amizi, Ayob (2019)
The participation of youth in the plantation sector, especially oil palm plantation in Malaysia is still low compared to other Southeast Asian countries. Many of them are less interested in choosing this job as a main career. This study used primary data collected by applying cluster and systematic random sampling techniques. Respondents involved in this study are youth aged 16 to 40 years old and living within five kilometres of the plantation. The data was analyzed using a probit model to identify factors that influence the probability to participate in oil palm plantation, while the Partial Least Square was used to measure causal factors affecting the level of happiness and job satisfaction among youths who were working and who had previously worked in oil palm plantation. Results of probit model show that age, gender, marital status, background in agriculture, race, religion, parent occupation, type of residence, wage policy and perceptions about social facilities, the social status of employment, and happiness and job satisfaction significantly affect local youths to participate in oil palm plantation sector. There is a significant difference in factors of influence on the probability to participate in oil palm plantations as temporary or permanent careers. The probability of local youths to choose a job in plantation as a permanent career was influenced by their perception on job happiness and satisfaction. However, perception on social status of employment significantly affects the probability of choosing it as a temporary career, Happiness and job satisfaction of those local youths who had previously worked in Sabah and Sarawak, and whom were working in Peninsular Malaysia appeared to be die most important factor that influence them to remain worldng or return to work in the oil palm sector. This study suggests for the government to put emphasize on happiness and job satisfaction, as well as the improvement of social facilities and social status of employment in order to encourage labor participation of local youth in plantation sector.